Penerapan Model Project Based Learning Berbantuan Media Audiovisual dalam Pembelajaran Menulis Teks Esai Siswa Kelas XII SMA Negeri 5 Sungai Penuh - Amelia Putri; Vivi Indriyani; Amril Amir; Abdurahman ((JPAP) Jurnal Praktisi Administrasi Pendidikan, 2026)
The purpose of this study is to describe the following: first, the planning of the implementation of the Project-Based Learning (PjBL) model assisted by audiovisual media in teaching essay writing to grade XII students at SMAN 5 Sungai Penuh; second, the implementation process of the PjBL model assisted by audiovisual media in teaching essay writing to grade XII students at SMAN 5 Sungai Penuh; and third, the evaluation of the implementation of the PjBL model assisted by audiovisual media in teaching essay writing to grade XII students at SMAN 5 Sungai Penuh. This study utilizes three main theories to analyze and discuss the findings: first, the learning of essay writing skills; second, the PjBL model assisted by audiovisual media; and third, the implementation of the PjBL model. This research employs a qualitative approach with a descriptive method. The data for this study include teaching modules, the essay writing learning process, and student worksheets (LKPD). The data sources, defined as the subjects from which data are obtained, include teachers, students, and the teaching and learning process. Data collection techniques used by the researcher are observation and interviews. The results of this study are threefold: first, thorough planning plays a crucial role in the successful implementation of the PjBL model assisted by audiovisual media; second, the implementation of the PjBL model assisted by audiovisual media increases student engagement in essay writing lessons; and third, the evaluation indicates that the PjBL method assisted by audiovisual media is more engaging compared to conventional methods. Thus, it can be concluded that the Project-Based Learning model assisted by audiovisual media has been effectively implemented in essay writing instruction for grade XII students at SMAN 5 Sungai Penuh.